Impact of DDoS Attacks on Different Services Using Various AQM Techniques - Singh, Arshdeep; Kaur, Lakhvinder; Singh, Kulwinder (International Journal of Computer Sciences and Engineering, 2025)
With the rapid development of network technology, distributed denial of service (DDoS) attacks become one of the most important issues. Distributed Denial of Service (DDoS) attacks generates enormous packets by a large number of agents and can easily exhaust the computing and communication resources of a victim within a short period of time. So congestion control mechanism is one of the key that keeps any network efficient and reliable for the users. Many mechanisms were projected in the literature over theses years for the efficient control of congestion that occur in the network. Active Queue Management (AQM) is one such mechanism which provides better control in the recent years. The focus of this work is to study the behaviors of various queuing algorithms such as Drop Tail, Fair Queuing (FQ), Stochastic Fair Queuing (SFQ), Deficit Round Robin (DRR) and Random Early Detection (RED) using ns-2 as a simulation environment.